Erratum to: The use of thermal hydrogen decrepitation to recycle Nd-Fe-B magnets from electronic waste, J. Min. Metall. Sect. B-Metall., 56 (3) (2020) 415-424. DOI:10.2298/JMMB200207032P - Piotrowicz, Andrzej; Pietrzyk, Stanisław; Noga, Piotr; Myćka, Łukasz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
/